1965
DOI: 10.1246/bcsj.38.1216
|View full text |Cite
|
Sign up to set email alerts
|

Concerning the Structure of Trimethyltin Fluoride

Abstract: The structure and the nature of the bonds in trimethyltin fluoride are discussed on the basis of the infrared and the Raman spectra with reference to the results of the X-ray diffraction study by Clark et al. and a few additional X-ray data obtained on the fluoride and related trimethyltin compounds. The most reasonable structure is one in which the planar trimethyltin group is bridged by the fluorine atom forming a non-linear unsymmetrical Sn-F…Sn bond. The distorted bipyramidal configuration around the tin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…2 Trimethyltin fluoride is insoluble in most organic solvents except in hot alcohols and melts upon decomposition at a relatively high temperature (375°C), which is strongly indicative of its aggregation in the solid state. 4 The second disorder model was also rejected upon careful reevaluation of the single crystal X-ray diffraction data which did not exhibit diffraction spots indicative of doubling in one cell axis, which is to be expected in the case of alternate tilting in successive Sn(CH 3 ) 3 groups. Clark et al reported that disorder precluded the proper refinement of its structure.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…2 Trimethyltin fluoride is insoluble in most organic solvents except in hot alcohols and melts upon decomposition at a relatively high temperature (375°C), which is strongly indicative of its aggregation in the solid state. 4 The second disorder model was also rejected upon careful reevaluation of the single crystal X-ray diffraction data which did not exhibit diffraction spots indicative of doubling in one cell axis, which is to be expected in the case of alternate tilting in successive Sn(CH 3 ) 3 groups. Clark et al reported that disorder precluded the proper refinement of its structure.…”
Section: Introductionmentioning
confidence: 99%
“…Trimethyltin fluoride was the first triorganyltin fluoride to be studied by X-ray crystallography; 3 however, the structural characterization proved to be problematic. 4 Hence, it was necessary to propose a new model with parallel planar SnC 3 moieties and positional disorder in the fluorine atoms with asymmetric fluorine bridges (Sn-F: 2.15 Å, Sn⋯F: 2.45 Å) and Sn-F⋯Sn and F-Sn⋯F angles of 141°. 3 Two possible disorder models were put forward, both invoking fluorine-bridged chain motifs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bridging occurs through halogen atoms or the oxoacid ligands. In the solid state, methyl tin halides (CH 3 ) 3 SnF , and (CH 3 ) 3 SnCl form extended halogen-bridged chains with pentacoordinate tin, while (CH 3 ) 2 SnF 2 has a sheetlike polymeric structure with hexacoordinate tin . The crystal structures of (CH 3 ) 2 Sn(SO 3 F) 2 , (CH 3 ) 3 SnOOCCF 3 , (C 6 H 12 ) 3 SnOOCC 3 H 7 , and (CH 3 ) 2 SnCl(OOCCH 3 ) 13 contain tin centers that are bridged by the oxoacid ligands.…”
Section: Introductionmentioning
confidence: 99%